Calcium- and Nitric Oxide-Dependent Nuclear Accumulation of Cytosolic Glyceraldehyde-3-Phosphate Dehydrogenase in Response to Long Chain Bases in Tobacco BY-2 Cells. (31st August 2016) - Testard, Ambroise; Da Silva, Daniel; Ormancey, Mélanie; Pichereaux, Carole; Pouzet, Cécile; Jauneau, Alain; Grat, Sabine; Robe, Eugénie; Brière, Christian; Cotelle, Valérie; Mazars, Christian; Thuleau, Patrice
Abstract: Sphinganine or dihydrosphingosine (d18:0, DHS), one of the most abundant free sphingoid long chain bases (LCBs) in plants, is known to induce a calcium-dependent programmed cell death (PCD) in plants. In addition, in tobacco BY-2 cells, it has been shown that DHS triggers a rapid production of H2 O2 and nitric oxide (NO). Recently, in analogy to what is known in the animal field, plant cytosolic glyceraldehyde-3-phosphate dehydrogenase (GAPC), a ubiquitous enzyme involved in glycolysis, has been suggested to fulfill other functions associated with its oxidative post-translational modifications such as S -nitrosylation on cysteine residues. In particular, in mammals, stress signals inducing NO production promote S -nitrosylation of GAPC and its subsequent translocation into the nucleus where the protein participates in the establishment of apoptosis. In the present study, we investigated the behavior of GAPC in tobacco BY-2 cells treated with DHS. We found that upon DHS treatment, an S -nitrosylated form of GAPC accumulated in the nucleus. This accumulation was dependent on NO production. Two genes encoding GAPCs, namely Nt(BY-2)GAPC1 and Nt(BY-2)GAPC2, were cloned. Transient overexpression of Nt(BY-2)GAPC–green fluorescent protein (GFP) chimeric constructs indicated that both proteins localized in the cytoplasm as well as in the nucleus. Mutating into serine the two cysteine residues thought to be S -nitrosylated in response to DHS did not modify the localization of the proteins, suggesting that S -nitrosylation of GAPCs was probably not necessary for their nuclear relocalization. Interestingly, using Förster resonance energy transfer experiments, we showed that Nt(BY-2)GAPCs interact with nucleic acids in the nucleus. When GAPCs were mutated on their cysteine residues, their interaction with nucleic acids was abolished, suggesting a role for GAPCs in the protection of nucleic acids against oxidative stress.